RISK FACTORS FOR ANEMIA IN PREGNANT WOMEN: LITERATURE REVIEW - Dwi Rukma Santi; Dewi Retno Suminar; Shrimarti R Devy; Mahmudah Mahmudah; Oedojo Soedirham (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Twenty percent (20%) of maternal mortality in developing countries is caused by iron deficiency anaemia. Meanwhile, the prevalence of anaemia in pregnancy in Asia is estimated at 48.2%, Africa 57.1%, America 24.1%, and Europe 25.1%. The trend of anaemia in pregnancy has increased in every years. To find out the risk factors that cause anaemia in pregnant women based on the research results in the health sector from 2014 to 2018. A literature review, by analyzing various studies regarding risk factors for anaemia in pregnant women. There are 17 studies from Indonesian and international researchers. From the results obtained, the educational factor is the most widely studied with a significant result (OR=2.467). Maternal factors that have significant influence are gestational age (OR=1.29) and nutritional status (OR=2.921), while nutrient intake factors that have a significant effect on anaemia in pregnant women are food intake (OR=2.54) and fluid intake (OR=2.91). Education level, nutritional status, food and beverage consumed are risk factors that have an effect on anaemia in pregnant women. Therefore, prevention measures for anaemia in pregnant women can be done by increasing maternal education and improving nutritional status with adequate nutrient intake.